ANALISIS FAKTOR PENYEBAB KECELAKAAN LALU LINTAS DI JALAN SUMBAR-RIAU KENAGARIAN SARILAMAK - Muhammad Andre; Helga Yermadona; Selpa Dewi (Ensiklopedia Research and Community Service Review, 2023)
On the West Sumatra-Riau highway, which is in Kenagarian Sarilamak, we can find quite severe road damage, namely uneven road surfaces and potholes, so accidents often occur. According to data from the Police in Lima Puluh Kota, the information was obtained that in the last four years there were 43 cases of accidents that resulted in property loss and human life. With these conditions, efforts are needed to determine the factors that cause traffic accidents and efforts to reduce accidents. The first step is to search for primary data by conducting a field survey to find out the cause of the accident. Secondary data was obtained from the Fifty City Police, namely data on the number of accidents in 2018-2021. From the analysis of the factors causing accidents, the human factor is in the highest category with an average percentage of 93.33% and the highest accident rate occurred in 2018, as many as 43 accident cases, with 3 people dead and 28 lightly injured. And from the correlation results, the results obtained that the number of incidents has a low correlation with a correlation value (r) of 0.168, and the severity of the victim is quite correlated with the number of accidents with a correlation value (r) of 0.96, and the cause of accidents is highly correlated with a correlation value of (r) 0, 96. Suggestions from this research are that the handling and awareness of humans as drivers and pedestrians needs to be improved.Keywords: traffic accident, factor of accident, correlation